1997
DOI: 10.1002/j.1834-4453.1997.tb00371.x
|View full text |Cite
|
Sign up to set email alerts
|

New Britain obsidian sources

Abstract: The natural occurrence of obsidian in volcanic flows in West New Britain has been thoroughly investigated and new measurements of the composition of field samples have been made with a proton dose of 150 l!C, increased by a factor of three compared to analyses reported in early studies. New data on precision and accuracy of PIXE-PIGME show that measurement error is not a significant factor in interpretations of chemical variability among source and artifact samples. The results provide evidence for 5 readily d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Although this island group is very important for the understanding of human colonisation of the Pacific, few archaeologists have visited it. Compared to the long successful history of volcanic glass provenance studies in the North-Western Pacific (Leach 1996;Ambrose 1978;Summerhayes 2003;Torrence et al 1996), which identified and unambiguously distinguished major sources and their exchange systems (Bird et al 1997;Duerden et al 1987;Torrence 2004;Specht 2002;White 1996), little is known about the distribution of northern Vanuatu volcanic glasses (Ambrose 1976).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although this island group is very important for the understanding of human colonisation of the Pacific, few archaeologists have visited it. Compared to the long successful history of volcanic glass provenance studies in the North-Western Pacific (Leach 1996;Ambrose 1978;Summerhayes 2003;Torrence et al 1996), which identified and unambiguously distinguished major sources and their exchange systems (Bird et al 1997;Duerden et al 1987;Torrence 2004;Specht 2002;White 1996), little is known about the distribution of northern Vanuatu volcanic glasses (Ambrose 1976).…”
mentioning
confidence: 99%
“…However, by focussing on single trace elements rather than case centroids (PCA results), the two source areas can be unambiguously separated. Figure 5 Previous extensive research on chemical fingerprinting volcanic glass sources in the Pacific has usually used PIXE-PIGME analyses (Bird 1996;Duerden et al 1987;Bird et al 1997;Summerhayes et al 1998), and the results are not directly comparable with the newly collected LA-ICP-MS data. Nevertheless, the comparison is important, and has been attempted here despite the previously mentioned difficulty in comparing data from micro-analytical techniques and bulk analysis and the consideration that, if results of two different methods of chemical characterisation are compared, a slight variation can be expected (Bellot-Gurlet et al 2005;Bugoi et al 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The New Britain obsidian source regions have been far better studied than the chert ones, with a growing literature on their distribution, geochemistry, age of formation, reduction strategies, production of special stemmed forms, and tool functions (Specht 1981;Torrence et al 1992Torrence et al , 2004aFullagar 1992Fullagar , 1993Bird et al 1997;Kealhofer et al 1999;Araho et al 2002;Rath and Torrence 2003;Torrence 2004bTorrence , 2005Kononenko 2007Kononenko , 2011Kononenko and Torrence 2009). Table 5 summarises the main features of the obsidian sources compared against those of the Passismanua chert.…”
Section: Comparison Between Obsidian and Chert Sourcesmentioning
confidence: 99%
“…Characterisation and sourcing of this obsidian has played a significant role in the examination of origins of lapita cultural patterns, changing patterns of regional interaction in the Bismarck Archipelago, long-distance transport and interaction in the lapita period, and chronology of resource use. Characterisation research has been popular since the late 1960s (Ambrose and Green 1972;Green 1998;Key 1968) and has made use of a wide variety of analytical methods, including emission spectroscopy (Key 1968), WD-XRF (Smith et al 1977), INAA (leach and Warren 1981), density (Green 1987;torrence and victor 1995), PIXE-PIGME Bird et al 1997;Summerhayes et al 1998) and most recently ICP-MS (Ambrose et al 2009) and Raman Spectroscopy (Carter et al 2009). Since the development in the 1980s of the use of PIXE-PIGME for the non-destructive characterisation of obsidian by Roger Bird at the lucas heights Research Facility in Sydney (ANStO), most geochemical characterisation of Pacific obsidians has been conducted using that technique.…”
mentioning
confidence: 99%